Absorption Boom and Fiscal Stance : What Lies Ahead in Eastern Europe? - Rahman, Jesmin (IMF Working Papers; Working Paper ;, 2010)
This paper estimates revenue and expenditure pro-cyclicality with respect to output and domestic absorption in new member states of the European Union and Croatia to assess whether these countries used the boom years of 2003-07 to create sufficient fiscal space. The current crisis has found many countries short of fiscal space. As these countries enter a different phase of capital inflows, some with large vulnerabilities and inflexible monetary policy options, the role of fiscal policy becomes more important. This paper also looks at these issues to see how fiscal policy can play a more effective role in demand management in these countries.